Insolubility and redistribution of GPI-anchored proteins at the cell surface after detergent treatment. - Mayor, S (1995)
A diverse set of cell surface eukaryotic proteins including receptors, enzymes, and adhesion molecules have a glycosylphosphoinositol-lipid (GPI) modification at the carboxy-terminal end that serves as their sole means of membrane anchoring. These GPI-anchored proteins are poorly solubilized in nonionic detergent such as Triton X-100. In addition these detergent-insoluble complexes from plasma membranes are significantly enriched in several cytoplasmic proteins including nonreceptor-type tyrosine kinases and caveolin/VIP-21, a component of the striated coat of caveolae. These observations have suggested that the detergent-insoluble complexes represent purified caveolar membrane preparations. However, we have recently shown by immunofluorescence and electron microscopy that GPI-anchored proteins are diffusely distributed at the cell surface but may be enriched in caveolae only after cross-linking. Although caveolae occupy only a small fraction of the cell surface (< 4%), almost all of the GPI-anchored protein at the cell surface becomes incorporated into detergent-insoluble low-density complexes. In this paper we show that upon detergent treatment the GPI-anchored proteins are redistributed into a significantly more clustered distribution in the remaining membranous structures. These results show that GPI-anchored proteins are intrinsically detergent-insoluble in the milieu of the plasma membrane, and their co-purification with caveolin is not reflective of their native distribution. These results also indicate that the association of caveolae, GPI-anchored proteins, and signalling proteins must be critically re-examined.